Health Psychology / Biopsychosocial Interactions: Sixth Edition - Sarafino Edward P (John Wiley And Sons, Inc, 2008)
An Introduction: Basic Issues and Processes, An Overview of Psychology and Health, The Body's Physical Systems, Stress and Illness and Coping, Stress - Its Meaning and Impact and Sources, Stress and Bopsychosocial Factors and Illness, Coping with and Reducing Stress, Lifestyles to Enhance Health and Prevent Illness, Health-Related Behavior and Health Promotion, Substance Use and Abuse, Nutrition and Wight Control and Diet and Exercise and Safety, Becoming Ill and Getting Medical Treatment, Using Health Services, In the Hospital: The Setting and Procedures and Effects on Patients, Physical Symptoms: Pain and Discomfort, The Nature and Symptoms of Pain, Managing and Controlling Clinical Pain, Chronic and Life-Threatening Health Problems, Serious and Disabling Chronic Illnesses: Causes and Management and Coping, Heart Diseas and Stroke and Cancer and Aids: Causes and Management and Coping, Looking to the Future, What's Ahead for Health Psychology?.